Agricultural development in the North-West Province of South Africa through the application of comprehensive project planning and appraisal methodologies - Van Rooyen, Cornelius Johannes (University of Pretoria, 2013)
Thesis (PhD (Rural Development Planning))--University of Pretoria, 2005.